Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Pemecahan Masalah dan Hasil Belajar Kognitif Siswa - Yunita, Lintang; Mandasari, Nining (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Based on the results of initial observations at SMA Negeri 7 Tangerang, it shows that students are less involved in the learning process, students tend to be passive, one of the factors that causes students to be less involved in learning is because the learning model and learning approach applied by the teacher is less varied. Therefore, research has been carried out on the influence of the Guided Inquiry learning model on problem solving abilities and cognitive learning outcomes of Biology students in Class XI SMA Negeri 7 Tangerang in the 2018/2019 academic year. The purpose of this study was to examine whether there was an effect of the Guided Inquiry learning model on problem solving abilities and cognitive learning outcomes of class XI students of SMA Negeri 7 Tangerang in the 2018/2019 academic year. The type of research used in this research is Quasi Experiment. The research design in this study was pre-test and post-test and the research sample was 19 students in class XI IPA 1 as the experimental class and 18 students in class XI IPA 2 as the control class. Collecting data using observation sheets to determine students' problem solving abilities, test sheets to determine cognitive learning outcomes. Based on data analysis, the average value of the control class for problem solving ability is 82.5% in the high category and the average value of the experimental class for problem solving ability is 90.62% in the very high category. The average value for cognitive learning outcomes for the control class is 77.2 while the average value for the experimental class is 85.7. Testing the hypothesis by using t-test analysis (t-test) at a significant level of 5% obtained a tcount value of 6.248 > ttable value of 1.684, so it can be concluded that there is an influence of the Guided Inquiry learning model on cognitive learning outcomes of class XI students at SMA Negeri 7 Tangerang in the academic year 2018/2019.